Changing Trade Relation of India & Pakistan: An Evaluation - Srivastava, Vivek Kumar; Kumar, Bhavtosh (Journal of Commerce and Trade, 2011)
Kautilya was the first one to write extensively on political economy. He theorized that to maintain a strong kingdom, the king must develop healthy relations with the neighbouring states through trade. When we talk about India, we can never ignore the Pakistan. India and Pakistan are the countries whose relations not only affect the economic relations of both the countries but also have some influence in the world politics. Pakistan is a neighbouring country of India. But the relationship of both the countries is bitter enough since 1947. Due to this there is extra burden on Indian economy on defence sector. If there is a good relationship it will be beneficial for growth and development of both the countries. So, there is a need to find out the solution of some major problems which exist between both the countries. An effort is made in this article to search out solutions of some big problems between India and Pakistan.